PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI PADA STEKOM SEMARANG - Kusumo, Haryo (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
This research aims to analyze the influence of organizational culture, work motivation, organizational commitment as a moderating variable and its impact on employee performance. The proposed hypothesis: Organizational culture has a significant effect on employee performance, work motivation that has a significant influence on employee performance, organizational commitment has a meaning to the performance of employees. The result of the research shows that organizational culture have positive and significant effect to employee performance, work motivation have positive and significant effect to employee performance, organizational commitment moderate positive influence of organizational culture to employee performance, organizational commitment moderate positive influence of work motivation toward employee performance.